A conceptual framework of assessing the impact of microcredit programmes on participants’ quality of life / Zuraidah Mohamed Isa - Mohamed Isa, Zuraidah; Ibrahim, Dahlia; Ali, Norhidayah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
Since the inception of the microcredit programmes, various studies have been carried out to assess their impacts. Earlier studies seemed to focus on the impact of microcredit on the participants’ income and consequently on poverty. However, recent studies of microcredit programmes have looked into the participants’ well-being instead of their income to measure their quality of life. Parallel to this, it was found that most of the studies assumed a direct relationship between microcredit programmes and participants’ quality of life. This assumption may not portray an accurate relationship between microcredit and quality of life. Hence, this study takes on a different perspective by examining aspects of personal attitude, subjective norms, perceived behavioural control, entrepreneurial intention and entrepreneurial behaviour in assessing the impact of microcredit programmes on participants’ quality of life. Conceptually, this paper shows that a comprehensive measure of quality of life is needed in assessing the impact of microcredit programmes.